PATH-23. OLIGOSARCOMA, IDH-MUTANT IS A DISTINCT AGGRESSIVE TYPE. (12th November 2021) - Suwala, Abigail K; Felix, Marius; Friedel, Dennis; Stichel, Damian; Schrimpf, Daniel; Hewer, Ekkehard; Schweizer, Leonille; Dohmen, Hildegard; Pohl, Ute; Erny, Daniel; Koelsche, Christian; Turner, Clinton; et al.
Abstract: Oligodendrogliomas are defined by IDH-mutations and the co-deletion of chromosomal arms 1p and 19q. In the past, case reports and small series described gliomas with sarcomatous features arising from oligodendrogliomas, so called oligosarcomas. Here, we report a group of 23 IDH-mutant oligosarcomas that form a distinct methylation group. The tumors were recurrences from prior oligodendrogliomas or developed de novo. Precursor tumors of 11 oligosarcomas were histologically and molecularly indistinguishable from conventional oligodendrogliomas. Tumor cells were embedded in a reticulin fibers network in all oligosarcomas, frequently showing p53 accumulation, positivity for SMA, and regain of H3K27me3 as compared to primary lesions. In 5 oligosarcomas no 1p/19q co-deletion was detectable, even though it was present in the primary lesions. Oligosarcomas harbored an increased chromosomal copy number variation load with frequent CDKN2A/B deletions. Proteomic profiling demonstrated oligosarcomas to be highly distinct from conventional grade 3 oligodendrogliomas with consistent evidence for smooth muscle differentiation. Expression of several tumor suppressors including NF1 and STAG2 was lost whereas oncogenic YAP1 was aberrantly overexpressed in oligosarcomas. Panel sequencing revealed mutations in TP53 and NF1 along with IDH1/2 and TERT promoter mutations. Survival of patients was significantly poorer for oligosarcomas as for grade 3 oligodendrogliomas but comparable to grade 4 IDH-mutant astrocytomas. These results establish oligosarcoma as a distinct type of IDH-mutant glioma differing from conventional oligodendrogliomas on the histologic, epigenetic, proteomic, molecular and clinical level. Diagnosis can be based on the characteristic DNA methylation profile or the combined evidence of sarcomatous histology, IDH-mutation and TERT promoter mutation with or without 1p/19q co-deletion.